Green Building Technology - G.Sharmilaa, Kale Priyanka, P.R.Kalyana Chakravarthy (International Journal of Advanced Science and Technology, 2020)
Shelter is one of the fundamental needs of humans. In the beginning of civilization, man used to live in caves and on trees; and gradually, invented latest technology with materials which helped him in construction of buildings. We, in order to make our buildings appealing, pay less attention to our surroundings. We are destroying native vegetation to construct more building and pathways which is resulting environment degradation and thereby, we experience problems like Global Warming. Today, shelter means more of Comfort and Healthy living standards. This must be combined with a care for nature – by using alternatives such as Green Buildings. Green Buildings consist of the four-Rs’ – Reduce, Reuse, Recycle, Renew.